Customer Satisfaction: Judging from Price, Product Quality and Service Quality: Study on Erigo's Customers - Oniek Ragil Puspitasari; Maulida Fitri Maisun; Arinal Haq; Muhammad Ibrahim Khuluqi; Riyan Andni; Lorena Dara Putri Karsono; Zaenuri Zaenuri; Zikra Jabben (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
By creating a research model and testing the three hypotheses proposed in this study, the purpose of this study is to examine how customer satisfaction is affected by price, product quality, and service quality. This study uses a type of quantitative research with primary data obtained from questionnaires or online surveys via the Google Form. The sample size of this study consisted of 100 respondents, namely Erigo customers who had purchased at least one product from the Erigo brand through Shopee e-commerce. The data analysis technique used is IBM SPSS Statistics 26 which includes validity and reliability tests, classical assumption tests, multiple linear regression analysis, F tests, T tests (hypotheses) and determinant coefficient. The results showed that price, product quality, and service quality had a positive and significant effect on Erigo's customer satisfaction. The results of this study will help other business actors in the same industry to make, implement and use the Erigo strategy to maintain business continuity more effectively.